Photocatalytic Water Splitting: Phase and Defect Engineering of MoS2 Stabilized in Periodic TiO2 Nanoporous Film for Enhanced Solar Water Splitting (Advanced Optical Materials 5/2019). Issue 5 (5th March 2019) - Guo, Limin; Zhong, Caifu; Shi, Li; Ju, Licheng; Wang, Xiaohui; Yang, Daquan; Bi, Ke; Hao, Yanan; Yang, Yang
Abstract : Periodically nanoporous MoS2 @TiO2 catalysts were designed to enhance the nonmetal plasmonic effect for solar H2 evolution. The phase transition from 2H‐ to 1T‐MoS2 coupled with the surface S vacancies is responsible for the enhanced localized surface plasmon resonance, leading to a superior H2 yield rate. The work by Ke Bi, Yanan Hao, Yang Yang and co‐workers (see article number 1801403 ) offers an innovative strategy to explore and improve nonmetal plasmonic catalysts with low cost and excellent durability, which is applicable in the renewable energy area.